An aspartic protease 47 causes quantitative recessive resistance to rice black-streaked dwarf virus disease and southern rice black-streaked dwarf virus disease - Zhaoyun Wang; Lian Zhou; Ying Lan; Xuejuan Li; Jian Wang; Jingfang Dong; Wei Guo; Dedao Jing; Qing Liu; Shaohong Zhang; Zhiyang Liu; Wenjuan Shi; et al. (Wiley, 2022)
Rice black-streaked dwarf virus disease (RBSDVD) and southern rice black-streaked dwarf virus disease (SRBSDVD) are the most destructive viral diseases in rice. Progress is limited in breeding due to lack of resistance resource and inadequate knowledge on the underlying functional gene.